Machine Failure Risk Management in Continuous Production Systems through Failure Mode Identification and Risk Priority Number Evaluation - Didit Darmawan; Dicky Setio Nugroho; Achmad Amirul Mufid; Muhammad Firdaus Hawari; Muhammad Hilal (Asosiasi Dosen Muda Indonesia, 2026)
Abstract: Machine failure risk management is essential in continuous production systems because unplanned downtime can disrupt production flow, reduce product quality, increase maintenance costs, and create safety risks. Objective: This study aims to develop a machine failure risk management framework through Failure Mode and Effects Analysis (FMEA) and Risk Priority Number (RPN) evaluation. Methodology: This research uses a qualitative literature study approach. Data were collected from scientific journals, technical standards, and academic publications related to reliability engineering, risk management, predictive maintenance, and production systems. The data were analyzed thematically to identify failure modes, risk assessment parameters, and effective control strategies. Findings: The findings show that machine failure risks can be managed through systematic identification of failure modes, evaluation of occurrence, severity, and detection, and prioritization based on RPN values. High-risk failure modes require preventive maintenance, predictive monitoring, redundancy systems, spare parts planning, and structured operator involvement. Implications: The proposed framework can assist manufacturing organizations in developing documented, auditable, and proactive maintenance risk management systems to improve machine reliability and reduce unplanned downtime. Originality: The originality of this study lies in integrating FMEA, RPN evaluation, predictive maintenance, spare parts management, operator participation, and ERP-based monitoring into a comprehensive framework for continuous production systems.